PifC and Osa, Plasmid Weapons against Rival Conjugative Coupling Proteins - Getino, María; Palencia-Gándara, Carolina; Garcillán-Barcia, M. Pilar; de la Cruz, Fernando (Frontiers in Microbiology, 2017)
Bacteria display a variety of mechanisms to control plasmid conjugation. Among them, fertility inhibition (FI) systems prevent conjugation of co-resident plasmids within donor cells. Analysis of the mechanisms of inhibition between conjugative plasmids could provide new alternatives to fight antibiotic resistance dissemination. In this work, inhibition of conjugation of broad host range IncW plasmids was analyzed in the presence of a set of co-resident plasmids. Strong FI systems against plasmid R388 conjugation were found in IncF/MOBF12 as well as in IncI/MOBP12 plasmids, represented by plasmid F and R64, respectively. In both cases, the responsible gene was pifC, known also to be involved in FI of IncP plasmids and Agrobacterium T-DNA transfer to plant cells. It was also discovered that the R388 gene osa, which affects T-DNA transfer, also prevented conjugation of IncP-1/MOBP11 plasmids represented by plasmids RP4 and R751. Conjugation experiments of different mobilizable plasmids, helped by either FI-susceptible or FI-resistant transfer systems, demonstrated that the conjugative component affected by both PifC and Osa was the type IV conjugative coupling protein. In addition, in silico analysis of FI proteins suggests that they represent recent acquisitions of conjugative plasmids, i.e., are not shared by members of the same plasmid species. This implies that FI are rapidly-moving accessory genes, possibly acting on evolutionary fights between plasmids for the colonization of specific hosts.